APPLICATION EXPERIENCE OF ALPROSTADIL FOR THE PATIENT, SUFFERING FROM SYSTEMIC LUPUS ERYTHEMATOSUS AND ANTI-PHOSPHOLIPID SYNDROME - E.I. Alexeeva; S.I. Valieva; A.E. Aleksandrov; S.A. Khmyzova (Педиатрическая фармакология)
The article deals with the clinical case of alprostadil application for the patient, suffering from systemic lupus erythematosus (SLE) and severe anti-phospholipid syndrome, which was complicated by the arterial thrombosis. The disease has been characterized by the high activity and aggressive run. The leading factor in the clinical picture was severe anti-phospholipid syndrome, which was complicated by the arterial thrombosis along with the growth of fore necrosis on the hand skin. The active treatment, which included synchronic therapy, glucocorticoids and medications, which improved blood circulation (pentoxifylline, dipiridamol, heparin), endovenous immunoglobulin transfusion had insufficiently reduced the activity of the disease and never inhibited thrombosis growth. The alprostadil application allowed cutting short the arterial thrombosis within the first hours and preventing growth of necrosis on the hand skin, as well as completely restoring the blood circulation in the affected parts of the hands. The findings of the clinical observation allowed the researchers to make a conclusion about effectiveness of a medication and possibility to use it among the patients, suffering from sle in children's rheumatologic practice.Key words: systemic lupus erythematosus, alprostadil, children, treatment.